Cerebral oxygen desaturation events during and functional outcomes after prehospital anaesthesia: A prospective pilot study. Issue 6 (7th April 2022) - Nurmi, Jouni; Laukkanen‐Nevala, Päivi; Kirves, Hetti; Raatiniemi, Lasse; Toivonen, Tuukka; Tommila, Miretta; Piiroinen, Heini; Setälä, Piritta; Karhivuori, Pamela; Tukia, Simo; Olkinuora, Anna
Abstract: Background: During prehospital anaesthesia, oxygen delivery to the brain might be inadequate to match the oxygen consumption, with unknown long‐term functional outcomes. We aimed to evaluate the feasibility of monitoring cerebral oxygenation during prehospital anaesthesia and determining the long‐term outcomes. Methods: We performed a prospective observational feasibility study in two helicopter emergency medical services units. Frontal lobe regional oxygen saturation (rSO2 ) of adult patients undergoing prehospital anaesthesia was monitored with near‐infrared spectroscopy (NIRS) by a Nonin H500 oximeter. The outcome was evaluated with a modified Rankin Scale (mRS) at 30 days and 1 year. Health‐related quality of life (HRQoL) was measured with a 15D instrument at 1 year. Results: Of 101 patients enrolled, 83 were included. The mean baseline rSO2 was 79% (73–84). Desaturation for at least 5 min to rSO2 below 50% or a decrease of 10% from baseline occurred in four (5%, 95% CI 2%–12%) and 19 (23%, 95% CI 15–93) patients. At 1 year, 32 patients (53%, 95% CI 41–65) achieved favourable neurological outcomes. The median 15D score was 0.889 (Q1–Q3, 0.796–0.970). Conclusion: Monitoring cerebral oxygenation with a hand‐held oximeter during prehospital anaesthesia and collecting data on functional outcomes and HRQoL are feasible. Only half of the patients achieved a favourable functional outcome. The effects of cerebral oxygenation on outcomes during prehospital critical care need to be assessed in future studies.